Sign Elements of International Food and Beverage Logos - Mitha Arfiana; T. Thyrhaya Zein; Nurlela (LingPoet: Journal of Linguistics and Literary Research, 2021)
This research entitled Sign Element of International Food and Beverage Logos. This research analyses the sign elements of food and beverage logos and the interpretation of the sign. The company want to promote and inform their product by creating the logo. This research applies the semiotic theory by Charles Sanders Peirce to analyse the sign elements and its interpretation in the logos. This research use qualitative descriptive method in analysing the data. The data is 7 food and beverage logos which goes international. Those 7 food and beverage logos are McDonald’s, Starbucks, Domino’s, Pizza Hut, KFC, Coca-Cola, and Pepsi. The data source in this research were logo images that collected from the logo’s official website and Wikipedia. This research will analyse the icon, index, and symbol of the logos as the sign elements by using Peirce’s triadic theory. Then the interpretation of the sign will analyze by relating the representment, object and interpretant. The result of this research shows that there are 6 icons, 5 indexes, and 7 symbols sign used in 7 food and beverage logos. There is 1 logo that has no icon sign, 2 logos have no index sign, and all logos have a symbol sign. The meaning of the sign elements that found in the logos was represented by relating the representment, object, and interpretant.